COVID-19 Pandemic: Care for Indian Cancer Patients - Kumar, Sandeep (Coronaviruses, 2021)
Background: Current COVID-19 pandemic poses a significant health crisis caused by SARSCoV- 2 coronavirus around the globe, including India. Patients with cancer, especially those who underwent treatment, may have a higher risk of getting sicker with COVID-19 disease. Medical care facilities aim to provide proper treatment to cancer patients while minimizing the possibilities of COVID-19 transmission. Objective: The perspective article summarizes practical recommendations and perspective answers to all difficulties so that we can better treat and care for cancer patients. Methods: The literature search includes recent publications and guidelines/recommendations of the central institutes of India. Results: Social distancing, guidelines, rescheduling the treatment of stable patients, nutritional care and telecommunication are some of the containment measures that can be applied in clinical practice in cancer management in COVID-19 pandemic. Conclusion: With these interventions discussed above, we can reduce the impact of this pandemic and deliver the best care to cancer patients.
Keywords: COVID-19